Getulio Alviani - Alviani, Getulio; Finessi, Beppe; Parmesani, Loredana; Pietrantonio, Giacinto Di (Italy; SKIRA, 2005)
Exhibition catalog. Oct 2004-Feb 2005 @ GAMeC, Galleria d'Arte Moderna Contemporanea Bergamo, Italy. One of the most important artists at an international level between the 1960s and the 1970s, a leading player in the art movement named variously as Optical Art and Kinetic Art or, as defined by Umberto Eco, Arte Programmata.
English; Italian
Keywords: N4390-5098 Exhibitions; Italy